2021
DOI: 10.31258/dli.8.2.p.147-153
|View full text |Cite
|
Sign up to set email alerts
|

Fitoakumulasi Logam Berat Pb dan Cr pada Rhizophora mucronata di Sekitar Kawasan Bekas Tambang Bauksit, Pulau Bintan

Abstract: Bintan Island has a high potential for bauxite mining. Many ex-mining areas have not been reclaimed properly, resulting in erosion and accumulation of heavy metals Pb and Cr which are high in the sediment (red-mud) and deposited in the roots of mangrove forests on the coast of Bintan. Rhizophora mucronata is one of the species that dominates the Bintan mangrove forest. The purpose of this study was to determine the phytoaccumulation of Pb and Cr metals in R. mucronata in the former bauxite mining area ofBintan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…On the other hand, it was reported that the sediment fraction in Carang River, Tanjungpinang City is dominated by sand (74.65-97.7%), while the Tembeling Tanjung and Wacopek in Bintan Regency are dominated by gravelly sand to slightly gravelly sand. 14 And also the survey results and sediment analysis, 13 the sediment fraction is dominated by sand and silt. This type of fraction is still classified as suitable for mangrove life, as evidenced by the results of observations in the field of mangrove life conditions that mangrove density is still found which is classified as rare to very dense.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…On the other hand, it was reported that the sediment fraction in Carang River, Tanjungpinang City is dominated by sand (74.65-97.7%), while the Tembeling Tanjung and Wacopek in Bintan Regency are dominated by gravelly sand to slightly gravelly sand. 14 And also the survey results and sediment analysis, 13 the sediment fraction is dominated by sand and silt. This type of fraction is still classified as suitable for mangrove life, as evidenced by the results of observations in the field of mangrove life conditions that mangrove density is still found which is classified as rare to very dense.…”
Section: Resultsmentioning
confidence: 95%
“…The reported values obtained from the analysis of metal contents in the area indicated non-compliance with the environmental quality standard. 12 The results from the previous study 13 showed that the environmental conditions around the former bauxite mining area on Bintan Island are not polluted but have been contaminated with heavy metals from mining activities. The conclusion was derived based on the Pollutant Load Index (PLI) value which was <1 for Pb and Cr, and the Geo-Accumulation Index (I_geo) which was 0<I_geo<1 for Pb and Cr.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations